2021
DOI: 10.1111/1755-0998.13561
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analyses of the genusDrosophilareveals genomic signals of climate adaptation

Abstract: Many Drosophila species differ widely in their distributions and climate niches, making them excellent subjects for evolutionary genomic studies. Here, we have developed a database of high‐quality assemblies for 46 Drosophila species and one closely related Zaprionus. Fifteen of the genomes were newly sequenced, and 20 were improved with additional sequencing. New or improved annotations were generated for all 47 species, assisted by new transcriptomes for 19. Phylogenomic analyses of these data resolved sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 169 publications
5
27
1
Order By: Relevance
“…As shown by Oliveira et al (2012) and Suvorov et al (2021), D. hydei represents the outermost branch of the repleta group clade. However, the positions of D. hydei and D. mercatorum in our tree are at odds with recent reports showing D. mercarotum as the most basal species of the clade (Li et al, 2021;Rane et al, 2019). Relationships within the buzzatii cluster in our tree are inconsistent with previous studies (Hurtado et al, 2019;Moreyra et al, 2019), particularly for the trio D. antonietae, D. borborema, and D. koepferae, which are representatives of the main lineages defined on grounds of fixed chromosomal inversions in the serido sibling set (Ruiz et al, 2000;Hasson et al, 2019).…”
Section: Phylogenomic Analysescontrasting
confidence: 99%
See 1 more Smart Citation
“…As shown by Oliveira et al (2012) and Suvorov et al (2021), D. hydei represents the outermost branch of the repleta group clade. However, the positions of D. hydei and D. mercatorum in our tree are at odds with recent reports showing D. mercarotum as the most basal species of the clade (Li et al, 2021;Rane et al, 2019). Relationships within the buzzatii cluster in our tree are inconsistent with previous studies (Hurtado et al, 2019;Moreyra et al, 2019), particularly for the trio D. antonietae, D. borborema, and D. koepferae, which are representatives of the main lineages defined on grounds of fixed chromosomal inversions in the serido sibling set (Ruiz et al, 2000;Hasson et al, 2019).…”
Section: Phylogenomic Analysescontrasting
confidence: 99%
“…Within the repleta group, species that belong to the mulleri subgroup are cactophilic whereas D. hydei and D. mercatorum are dietary generalists with the ability of feeding upon rotting fruits, vegetables, and cacti. Note that the D. mercatorum genome included in our study was originally reported as D. repleta by Rane et al (2019) and assigned to the proper species by (Li et al, 2021). The genomes of D. virilis (virilis group, subgenus Drosophila), sister of the repleta group, and D. melanogaster as the only representative of the subgenus Sophophora were also included in the study (Throckmorton, 1975;Clark et al, 2007).…”
Section: Species Selectionmentioning
confidence: 99%
“…We expanded the species sampled to include three closely related species from the yakuba complex: D. yakuba, D. santomea , and D. teissieri . We also took advantage of published population genomic data from samples of inbred lines to expand our assessment of bam variation in additional population samples for D. melanogaster (Lack et al 2015) and D. simulans and to newly assess bam variation in population samples in the montium species group ( D. serrata, D. bunnanda, D. birchii , and D. jambulina ) and the ananassae species subgroup ( D. bipectinata, D. pseudoananassae , and D. pandora ) (Li et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We thank Daniel Matute, Brandon Cooper, Robert Unckless, Erin Kelleher, and Luciano Matzkin for the population samples they provided for this study. We thank Fang Li for working to make the variant call files from (Li et al 2021) quickly available for this study.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation